Do they shop to stand out or fit in? The luxury fashion purchase intentions of young adults. Issue 3 (9th February 2018) - Eastman, Jacqueline K.; Iyer, Rajesh; Shepherd, C. David; Heugel, Angelina; Faulk, Don
Abstract: A three‐study examination of young adults suggests that their motivation for status in terms of their luxury fashion purchase intentions is impacted by a bandwagon effect. In Study 1, qualitative research informs what fashion items represent status to young adults, how they view these items, and how they view others owning these items. In Study 2, survey research establishes the link between the motivation for status (status consumption) and purchase intention/ownership of these fashion items. In Study 3, a national survey of young adults examines what mediates and moderates the motivation for status to lead to luxury fashion purchase intentions. Results from the three studies indicate that status consumption has a positive impact on purchase intention of luxury fashion. This research also finds that cultural variables have an impact (mediate) the relationship between status consumption and purchase intention. Specifically, collectivism, uncertainty avoidance, power distance, and masculinity mediate the relationship between status consumption and purchase intention. Finally, the moderating impact of the bandwagon effect has a significant effect on the relationship between status consumption and fashion purchase intention for the cultural variables of uncertainty avoidance, long‐term orientation, and power distance. Implications for marketers are provided based on the findings.